A geografia dos óbitos causados por transporte terrestre na Amazônia Legal: uma análise do período de 2009 a 2013 - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The increase in the rate of motorization is one of the main causes of the increase in deaths due to Road Traffic Accidents - RTA in Brazil. This is recognized as an important factor, but it is believed that it is necessary to evaluate the realities that characterize each regional and local context. Unlike the rest of the country, the Legal Amazon presents a geographic configuration with patterns of cities whose genesis occurred on the margins of navigable rivers, and some of these still remain until the present day accessed only by waterway transportation. On the other hand, more recently, a network of highways was implanted in the region, giving rise to new urban centers to its banks. The present research was based on these differences in the type of access to the municipalities' headquarters in order to understand the distribution of occurrences of deaths by RTA in the region. Taking into account these singularities, this dissertation had as a general objective to analyze the relationship between the different types of access to cities, the distribution of the population, the fleet of vehicles and the cumulative number of occurrences by RTA in the period 2009-2013. The data used in the research were from the Sistema de Informação de Mortalidade (Mortality Information System) of the Sistema Unificado de Saúde (Unified Health System) - SIM / SUS, corresponding to the sum of the period, the population of 2010, made available by the Instituto Brasileiro de Geografia e Estatística (Brazilian Institute of Geography and Statistics) - IBGE, the vehicle fleet of 2013, from the Departamento Nacional de Infraestrutura (National Department of Infrastructure) - DNIT. The alphanumeric data were prepared in electronic spreadsheets and imported into a Geographic Information System (GIS) to generate thematic maps about the region. The results indicate that the municipalities with road link have a higher ratio of vehicles per inhabitant and, consequently, a greater number of deaths by RTA than those located on the river banks. A strong correlation was found between the variables analyzed, with the populous municipalities and with the largest vehicle fleet having the highest rates of RTA victims in the Legal Amazon.
Keywords: Amazônia Legal; Frota de veículos; Transporte terrestre - Acidentes; CIÊNCIAS HUMANAS: GEOGRAFIA